Soil treatment in flood areas: case of the road RP4209, in the province of Kenitra (Morocco) - Sebbar N.; Lahmili A.; Ouadif L.; Akhssas A.; Bahi L. (MATEC Web of Conferences, 2018)
The Moroccan road network has a linear of more than 57,000 km divided into national, regional, provincial and unclassified roads. Population growth, the transport of goods and the mobility of people require the construction of new links between regions and the maintenance of existing ones. Indeed, several factors, such as rainfall and floods, can cause enormous damage to existing infrastructure. Among the most at-risk areas is the GHARB region, especially the province of Kénitra, represented in this study by Provincial Road RP4209, which includes flood-prone areas with abundant watercourses, associated with poor type of soil. To mitigate these phenomena and to try to reduce their impacts, in particular on the components of a road, one of the appropriate solutions remains the treatment of soils. This process is increasingly practiced in the construction industry, improves the geotechnical and mechanical characteristics of soils without having to go through the contribution of materials from other regions, all for the purpose of a valuation of materials in place by treatment with lime, different hydraulic binders, or industrial products, which will provide an economic and environmental gain